On the interaction of small molecules with hemoproteins: Sperm whale myoglobin - Baffa, O.; Tabak, M.; Nascimento, O. R.; Ruggiero, J. [UNESP] (Springer Nature, 1985)
The spin label TEMPO does not show a binding to myoglobin molecule in solution. This is probably due to the fact that this protein does not have a hydrophobic pocket large enough to accommodate the TEMPO molecule. In the crystal the spin label is bound and two kinds of spectra are observed: one isotropic and the other anisotropic. The anisotropic site is probably an intermolecular one. The correlation time for the label in the crystal is very sensitive to temperature showing a transition near 30 °C. This change can be explained as a result of the conformational change observed for myoglobin near this temperature: the motion of the spin label becomes more restricted below this temperature. Change in hydration is the probable cause of this structural change. The changes in the EPR spectra of the anisotropic label suggest that it is bound near the first layers of protein in the crystal. © 1985 Societá Italiana di Fisica.
Keywords: Molecular biophysics